Evaluation of the efficiency of magnets in deflecting Ag-atoms in the PBmr-Magnetic Isotope (MIS) - Mokgantshang, Joyce Keneilwe (North-West University (South Africa), 2008)
The South-African Pebble Bed Modular Reactor (PBMR) is a high temperature gas cooled reactor (HTGCR) which uses the inert gas helium as a coolant and coated particles as fuel. The design of these coated particles is such that they are able to form a protective barrier against the release of radioactive fission products up to a temperature of 1600 °C under the reactor operating conditions (Ogawa T., et al. 1985). It has been observed from the already proven fuel that the coating layers of these coated particles are not effective against the release of silver (Heather J.M., Ronald G.B., 2004). Of great concern is the release of Ag-1 l0m which has a half-life of 253 days and is an /3- r emitter when decaying to its Cd stable state (Leena Joseph, et al., 2007). The released silver is therefore able to enter into the helium gas which is circulating through the reactor power conversion circuit and upon reaching the cooler sides, silver will start to plate out. This constitutes a maintenance problem as ten half-lives have to elapse before normal maintenance can be done. This also poses a radiation hazard to operating personnel and to the members of the public in case of accidental leakage of helium into the environment. This has led to the proposal of the installation of the Magnetic Isotope Scrubber (MIS) into the hot-pipe section of the reactor in order to remove silver from helium before entering into the Power Conversion Unit (PCU). The scrubber will consist of two components: magnets, either permanent or electro-magnetic, to produce the magnetic field needed to deflect silver atoms, and an atom catcher to catch and contain the radioactive silver atoms. The technique is based on the Stem-Gerlach principle. The focus of this study was therefore to determine the efficiency of magnets in deflecting silver atoms to a specified position. This was achieved by designing and manufacturing a Magnetic Scrubber Model (MSM), and using it to study the efficiency of magnets. In the experiment a beam of silver atoms was created in an oven by evaporating 99.99 % pure silver pellets at a temperature of ± 600 °C under a vacuum pressure of 1 x 10 -5 Torr. The beam was collimated to 2 mm and was allowed to enter the flight tube surrounded by magnets thereby hitting the target which was placed at a specified position. The magnets used were permanent rare earth magnets know as NIB (Neodymium, Iron, Boron) and were orientated to produce a magnetic field intensity of 0.5 Tesla (T) in the centre of the flight tube. The deflection of silver was carried out at different target positions, 12.5, 25.0, 37.5, 50.0 and 75.0 mm with reference to the oven exit and corresponding magnet lengths were used. The obtained results showed that at shorter distances and shorter magnet lengths the Agatoms are less or not at all deflected whereas at longer target position and longer magnets they are strongly deflected. It is therefore concluded that it is important to carry out the deflection over a long range to allow for greater deflection of Ag-atoms.
MSc (Applied Radiation Science and Technology), North-West University, Mafikeng Campus